Molecular Docking of Arjuna Tree Phytocompounds for Ischemic Heart Disease - Amulya Rao T (International Journal of Bioinformatics and Computational Biology, 2025)
Heart disease is a serious condition that can be caused by several lifestyle changes and sometimes genetic problems. The primary protein component of apolipoprotein is the LDL receptor, which indicates that a reduction in LDL levels can reduce the risk of ischemic heart disease. Apolipoprotein levels are associated with increased levels of ischemic heart disease. Using ADMET analysis, drug likelihood prediction, and molecular docking, this work attempted to find natural chemicals from Terminalia arjuna (T. arjuna) that have several medicinal uses in Indian Ayurveda to prevent disease. The PDB database provided the 3D structure of the apolipoprotein, while the PubChem database provided 2D SDF format for the phytocompounds from T. arjuna. The Pyrx tool was used to analyse and remove the ligands with low binding affinity and was used for docking. BIOVIA Visualizer was used for visualization. The statistical distribution of the combinations of the protein’s backbone dihedral angles ϕ and ψ is displayed via Ramachandran plot analysis. Five chemicals from T. arjuna have been identified by molecular docking experiments as having the capacity to attach to the apolipoprotein. Five compounds were found to have drug-like qualities based on the ADMET profile and drug likeness prediction. According to the current study, two chemicals have distinct binding affinities and may be employed as ischemic heart disease therapeutic strategies.
Keywords: ADMET; Apolipoprotein; CHD; Pyrx tool; Terminalia arjuna; molecular docking